Integrating hydrological impacts for cost-effective dryland ecological restoration - Fengyu Fu; Shuai Wang; Xutong Wu; Shiyin Chen; Zimin Tan; ChongChong Ye; José M. Grünzweig (Communications Earth & Environment)
Abstract Ecological restoration of fragile drylands involves complex benefit-cost trade-offs. While Systematic Conservation Planning (SCP) provides a foundational framework for this task, its large-scale application in drylands often fails to adequately integrate critical hydrological impacts, notably ecosystem water consumption. Here, we developed and applied an integrated SCP framework to optimize spatial prioritization for ecological restoration in China’s drylands. This framework explicitly integrates water cost, calculated as increased ecosystem evapotranspiration via the Budyko model, and economic costs based on statistical data. It also assessed benefits, including habitat increases for 3,005 species and enhanced biomass carbon sequestration. Our proposed integrated pathway minimizes water cost while ensuring cost-effectiveness, on average, achieving 81.0% of the maximum potential biomass carbon sequestration and 88.1% of the maximum potential habitat area increases. Compared to scenarios focusing solely on economic costs, this approach reduces the average cumulative water cost by 27.0% and the maximum cumulative water cost by 91.1%. This stark contrast demonstrates that focusing on economics alone leads to misaligned spatial restoration priorities, underscoring the necessity of integrating ecosystem water consumption into dryland SCP. Our findings not only establishe a decision-making foundation for China but also offer a generalizable multi-criteria framework for cost-effective dryland restoration worldwide.